Microstructure and Properties of Ag-Doped ZnO Grown Hydrothermally on a Graphene-Coated Polyethylene Terephthalate Bilayer Flexible Substrate - Ai, Taotao; Fan, Yuanyuan; Wang, Huhu; Zou, Xiangyu; Bao, Weiwei; Deng, Zhifeng; Zhao, Zhongguo; Li, Miao; Kou, Lingjiang; Feng, Xiaoming; Li, Mei (Frontiers in Chemistry, 2021)
Composite structures comprising Ag-doped ZnO films on a PET-graphene substrate (Ag-ZnO/PET-GR) with different Ag doping concentrations were synthesized by low-temperature ion-sputtering-assisted hydrothermal synthesis method. The phase composition, the valence states, morphology and structure, forbidden band gap, and electrical properties of surface elements, and the photocatalytic activity for the degradation of methylene blue solution were analyzed. Ag doping affects the initially perpendicular growth of ZnO nanorods, with the effect of oblique growth becoming more obvious as the Ag content increases, and the diameter of the nanorods decreasing gradually. The width of the forbidden band gap of the ZnO films decreases with increasing Ag content. For the Ag-ZnO/PET-GR composite structure, the Ag-ZnO thin film doped with 5% Ag has the largest carrier concentration (8.1 × 1018 cm−3), the highest mobility (67 cm2∙V-1∙s-1), a small resistivity (0.09 Ω·cm), and impressive electrical properties.